KONTRIBUSI MOTIVASI BERPRESTASI DAN SISTEM PENGHARGAAN TERHADAP KEPUASAN KERJA GURU SDN KECAMATAN LANGGAM KABUPATEN PELALAWAN - Zulfahmi Zulfahmi; Isjoni Isjoni; Azhar Azhar (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2022)
This research aims to (1) know pedagogical competencies affect teacher performance, (2) work motivation affects teacher performance, (3) pedagogical competence and work motivation affects jointly on teacher performance. The study respondents were teachers of The State Elementary School in Langgam District of Pelalawan Regency which amounted to 269 people with a sample of 161. Data collection is carried out through the dissemination of questionnaires. The data analysis used is descriptive analysis, inferential statistical analysis. The coefficient of reliability of the instrument is calculated using the alpha cronbach formula. The results showed a positive and significant influence of pedagogical competence on teacher performance of 0.524, and there was a positive and significant influence of work motivation on teacher performance of 0.638. While together there is the influence of pedagogical competence and work motivation on teacher performance by 0.730.